Immune analysis of lymph nodes in relation to the presence or absence of tumor infiltrating lymphocytes in triple-negative breast cancer. (May 2021) - Quintana, Ángela; Peg, Vicente; Prat, Aleix; Moliné, Teresa; Villacampa, Guillermo; Paré, Laia; Galván, Patricia; Dientsmann, Rodrigo; Schmid, Peter; Curigliano, Giuseppe; Muñoz-Couselo, Eva; Perez-García, José; et al.
Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer with unmet medical needs. Several studies have proved that high levels of tumor infiltrating lymphocytes (TILs) at diagnosis of TNBC confer better prognosis and patients respond better to specific chemotherapies. Nonetheless, current evidence suggests that only 15% of TNBC patients have very high levels of TILs, and another 15% lacks TILs. One possible reason to explain why patients have low TILs at diagnosis is that lymphocytes might be deactivated by an immune checkpoint in local lymph nodes, provoking their retention in there as they are unresponsive to other immune stimuli. We have identified 15 high TILs (≥50%) and 20 low TILs (≤5%) TNBC patients with localised tumour (T1c-T2N0M0) and compared the protein expression of five immune checkpoints in lymph nodes. We have also performed a customised 50-immune gene NanoString expression panel, the NanoString 360 Breast Cancer panel, and whole exome sequencing for mutation and neoantigen load analyses. In low TILs, we observed higher expression of CTLA-4 in local lymph nodes, which could explain why lymphocytes get retained in there and do not migrate to tumour. These patients have also higher neoantigen load and higher expression of B7.H3 and B7.H4 in the tumour. In high TILs, we observed more PD-L1+ tumour cells and more expanded humoral response. These results could provide a strategy to revert low tumour immune infiltration at diagnosis of TNBC, improving their prognosis. Highlights: High levels of TILs are associated with higher PFS and OS in TNBC. About 15% of TNBC patients presents high levels of TILs at diagnosis. In low TILs group, higher expression of CTLA-4 in local lymph nodes of TNBC was observed. Higher neoantigen load and expression of B7.H3 and B7.H4 were observed in low TIL tumours. In high TILs, more PD-L1+ tumour cells and more expanded humoral response were observed.